The Time Is Ripe for Entrepreneurship in Vocational Rehabilitation: A Four-Pronged Approach. (April 2023) - Frain, Michael; Bishop, Malachy; Frain, Julianne; Rohack, Devin; Shirley, Ghari; Sánchez, Jennifer
The field of rehabilitation has laid a great foundation for the monumental entrepreneurial changes that have occurred to the worldwide economy due to the COVID-19 pandemic. The use of self-employment as an outcome has fallen below 1% of Vocational Rehabilitation closures but can rise as the field takes a four-pronged approach to helping individuals become entrepreneurs. The idea of entrepreneurship fits rehabilitation philosophy, and through training, legislation, and new vision many persons with disabilities can find successful careers as entrepreneurs.